Pengaruh Plyometric Exercise Single Leg Hop dan Double Leg Hop terhadap Peningkatan Power Tungkai : A Systematic Literature Review - Farah Nandiva Tiamanda; Riza Pahlawi (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Plyometric training is an effective training method in increasing muscle power, especially in the lower body which is very much needed in various sports. This study aims to examine the effectiveness of two types of plyometric training, namely Single Leg Hop and Double Leg Hop, on increasing leg muscle power. The study was conducted using a literature review approach to eight previous relevant studies. The results of the review showed that both types of training had a positive and significant effect on increasing leg muscle power. However, most studies concluded that Single Leg Hop training was superior in increasing unilateral strength and specific muscle explosive power, especially in sports such as futsal, basketball, and long jump. Thus, Single Leg Hop training can be recommended as a more effective method for developing lower muscle power, although the selection of training types still needs to be adjusted to the characteristics and needs of athletes.